Family Caregivers Challenges for Stroke Survivors in the Community: A Literature Review - Israfil, Israfil; Wulandari, Sarah Kartika; Suyasa, I Gede Putu Darma; Indrayani, Ni Luh Dwi; Agustini, Ni Luh Putu Inca Buntari (Borneo Scientific Publishing, 2026)
Stroke is a chronic condition that significantly reduces the patient's quality of life and increases the need for support from family caregivers. This situation places the family as a crucial element in patient care, yet often presents significant challenges for family caregivers. This study aims to identify and describe the various challenges faced by families caring for stroke patients in the community. A literature review design was employed. Relevant articles published between 2020 and 2025 were retrieved from international databases including PubMed and ScienceDirect, using the keywords